1975
DOI: 10.1083/jcb.65.2.286
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular materials in cell movement. I. Inhibition of mucopolysaccharide synthesis does not stop ruffling membrane activity or cell movement.

Abstract: The involvement of mucopolysaccharide synthesis in cell locomotion was investigated by determining the effects of inhibition of synthesis on ruffling membrane activity and cell movement by embryonic heart fibroblasts. Mucopolysaccharide synthesis was inhibited directly by treatment with a glutamine analog, 6-diazo-5-oxo-L-norleucine (DON), and indirectly with cycloheximide. DON treatment reduced synthesis to 20% of control values, and cycloheximide reduced synthesis to less than 10% of control values, as measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 42 publications
4
1
0
Order By: Relevance
“…The behavioral differences evident at low density probably do not involve differences in cell surface GAG because, although there is a small difference in amount, the types and relative proportions of labeled surface GAG on low density 3T3 and 3T3SV cells are very similar. This conclusion is consistent with the report that cell locomotion is not modified by inhibition of GAG synthesis (44).…”
Section: Relationship Of Culture Behavior To Gag Distributionsupporting
confidence: 94%
“…The behavioral differences evident at low density probably do not involve differences in cell surface GAG because, although there is a small difference in amount, the types and relative proportions of labeled surface GAG on low density 3T3 and 3T3SV cells are very similar. This conclusion is consistent with the report that cell locomotion is not modified by inhibition of GAG synthesis (44).…”
Section: Relationship Of Culture Behavior To Gag Distributionsupporting
confidence: 94%
“…A similar pattern of inhibition was found with DON (6-diazo-5-oxo-L-norleucine), a glutamine analog that is thought to inhibit mucopolysaccharide synthesis (37,39). Recovery was partially affected by DON (Table I), and collection of recovered cells was unaffected by DON at a concentration that inhibited incorporation of [asS]sulfate into mucopolysaccharides by about 70% (37). The inhibition pattern of DON was very similar to that of cycloheximide: both inhibitors affected the recovery of cells from trypsin treatment but did not completely inhibit recovery.…”
Section: Affected By Inhibitorssupporting
confidence: 56%
“…If ceils were given a chance to recover before cycloheximide treatment (Table II), the cycloheximide had little or no effect on the rate of collection for 2 h. We have previously shown that long treatments with cycloheximide eventually inhibit collection of recovered cells (18). A similar pattern of inhibition was found with DON (6-diazo-5-oxo-L-norleucine), a glutamine analog that is thought to inhibit mucopolysaccharide synthesis (37,39). Recovery was partially affected by DON (Table I), and collection of recovered cells was unaffected by DON at a concentration that inhibited incorporation of [asS]sulfate into mucopolysaccharides by about 70% (37).…”
Section: Affected By Inhibitorssupporting
confidence: 55%
“…A similar time-dependent inhibition of [35S]sulphate incorporation by DON has been reported for cultures of chick heart fibroblasts (Spooner & Conrad, 1975).…”
Section: Discussionsupporting
confidence: 79%